Solve for g (complex solution)
\left\{\begin{matrix}g=\frac{\left(7x-6\right)\left(x+1\right)}{6yx^{2}}\text{, }&x\neq 0\text{ and }y\neq 0\text{ and }x\neq -1\\g\in \mathrm{C}\text{, }&x=\frac{6}{7}\text{ and }y=0\end{matrix}\right.
Solve for g
\left\{\begin{matrix}g=\frac{\left(7x-6\right)\left(x+1\right)}{6yx^{2}}\text{, }&x\neq 0\text{ and }y\neq 0\text{ and }x\neq -1\\g\in \mathrm{R}\text{, }&x=\frac{6}{7}\text{ and }y=0\end{matrix}\right.
Solve for x (complex solution)
\left\{\begin{matrix}x=-\frac{\sqrt{169-144gy}-13}{12gy+\sqrt{169-144gy}-13}\text{, }&y\neq 0\text{ and }g\neq 0\\x=\frac{\sqrt{169-144gy}+13}{12gy-\sqrt{169-144gy}-13}\text{, }&g\neq \frac{7}{6y}\text{ and }y\neq 0\text{ and }g\neq 0\\x=\frac{6}{7}\text{, }&y=0\text{ or }g=0\end{matrix}\right.
Graph
Share
Copied to clipboard
6xgyx+\left(6x+6\right)\left(x+1\right)=13x\left(x+1\right)
Multiply both sides of the equation by 6x\left(x+1\right), the least common multiple of x+1,x,6.
6x^{2}gy+\left(6x+6\right)\left(x+1\right)=13x\left(x+1\right)
Multiply x and x to get x^{2}.
6x^{2}gy+6x^{2}+12x+6=13x\left(x+1\right)
Use the distributive property to multiply 6x+6 by x+1 and combine like terms.
6x^{2}gy+6x^{2}+12x+6=13x^{2}+13x
Use the distributive property to multiply 13x by x+1.
6x^{2}gy+12x+6=13x^{2}+13x-6x^{2}
Subtract 6x^{2} from both sides.
6x^{2}gy+12x+6=7x^{2}+13x
Combine 13x^{2} and -6x^{2} to get 7x^{2}.
6x^{2}gy+6=7x^{2}+13x-12x
Subtract 12x from both sides.
6x^{2}gy+6=7x^{2}+x
Combine 13x and -12x to get x.
6x^{2}gy=7x^{2}+x-6
Subtract 6 from both sides.
6yx^{2}g=7x^{2}+x-6
The equation is in standard form.
\frac{6yx^{2}g}{6yx^{2}}=\frac{\left(7x-6\right)\left(x+1\right)}{6yx^{2}}
Divide both sides by 6x^{2}y.
g=\frac{\left(7x-6\right)\left(x+1\right)}{6yx^{2}}
Dividing by 6x^{2}y undoes the multiplication by 6x^{2}y.
6xgyx+\left(6x+6\right)\left(x+1\right)=13x\left(x+1\right)
Multiply both sides of the equation by 6x\left(x+1\right), the least common multiple of x+1,x,6.
6x^{2}gy+\left(6x+6\right)\left(x+1\right)=13x\left(x+1\right)
Multiply x and x to get x^{2}.
6x^{2}gy+6x^{2}+12x+6=13x\left(x+1\right)
Use the distributive property to multiply 6x+6 by x+1 and combine like terms.
6x^{2}gy+6x^{2}+12x+6=13x^{2}+13x
Use the distributive property to multiply 13x by x+1.
6x^{2}gy+12x+6=13x^{2}+13x-6x^{2}
Subtract 6x^{2} from both sides.
6x^{2}gy+12x+6=7x^{2}+13x
Combine 13x^{2} and -6x^{2} to get 7x^{2}.
6x^{2}gy+6=7x^{2}+13x-12x
Subtract 12x from both sides.
6x^{2}gy+6=7x^{2}+x
Combine 13x and -12x to get x.
6x^{2}gy=7x^{2}+x-6
Subtract 6 from both sides.
6yx^{2}g=7x^{2}+x-6
The equation is in standard form.
\frac{6yx^{2}g}{6yx^{2}}=\frac{\left(7x-6\right)\left(x+1\right)}{6yx^{2}}
Divide both sides by 6x^{2}y.
g=\frac{\left(7x-6\right)\left(x+1\right)}{6yx^{2}}
Dividing by 6x^{2}y undoes the multiplication by 6x^{2}y.
Examples
Quadratic equation
{ x } ^ { 2 } - 4 x - 5 = 0
Trigonometry
4 \sin \theta \cos \theta = 2 \sin \theta
Linear equation
y = 3x + 4
Arithmetic
699 * 533
Matrix
\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { -1 } & { 1 } & { 5 } \end{array} \right]
Simultaneous equation
\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.
Differentiation
\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }
Integration
\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x
Limits
\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}